UNDERSTANDING COMMON ERRORS IN LINEAR EQUATIONS SYSTEMS AMONG EIGHT GRADE STUDENTS - Ikfini, Ikfini Aulia Hakika; Nurharunawati, Nurhanurawati; Rumite, Wayan (KALAMATIKA Jurnal Pendidikan Matematika, 2024)
This research employs a qualitative descriptive method. The average student score in the first semester final summative assessments indicates that the minimal completion criteria have been met; however, a review of the list of incorrect responses shows that many of the errors are related to two-variable linear equation systems. Additionally, it is common for students to struggle with converting a mathematical model from the problem. The purpose of this study is to describe the errors made by students in solving problems related to two-variable linear systems and to analyze the factors contributing to these errors. We used data analysis of student responses in this study because it allows us to observe the students' thought processes and ensures the accuracy of the information. According to the study's findings, students' errors in answering the questions stemmed from their inability to grasp relevant concepts. One possible solution is for students who struggle with conceptual understanding to focus more on mastering the material, practice answering questions frequently to become accustomed to various question types, and ultimately enhance their comprehension of mathematical concepts.